Effect of Multi-trace Elements Supplementation on Biochemical Markers and Postoperative Outcome in Patients Undergoing Elective Cardiac Surgery - Amirizadeh, Mehran; Eslami, Gohar; Shafaei-Bajestani, Negar; Soleimani, Aria; Habtemariam, Solomon; Hashemi, Javad; Sahebnasagh, Adeleh (Recent Advances in Inflammation & Allergy Drug Discovery, 2025)
Background: Coronary Artery Bypass Graft (CABG) surgery is employed to increase the lifespan of patients with Coronary Artery Disease (CAD). The low serum levels of essential elements have a negative effect on patients undergoing CABG.Objective: This clinical trial aimed to investigate the effect of trace elements supplements on postoperative outcomes after coronary artery bypass graft.Methods: Two hundred patients underwent on-pump CABG to randomly receive either Addamel©, which contains essential trace elements, or isotonic saline for 3 days. We measured postoperative plasma Zn, Se, Cu, Mn, Se, and Fe concentrations, and the levels of highly sensitive C-reactive Protein (hs-CRP) on days 0, 1, and 2. Duration of hospital and Intensive Care Unit (ICU) stay, 30-day mortality, and the incidence of Arterial Fibrillation (AF) have been evaluated as secondary outcomes.Results: In the supplemented group, the plasma levels of Cu and Mn increased by day 3, and plasma hs-CRP increased by day 1 in both groups, but it decreased in patients who received trace elements supplementation on day 2. The Addamel group had a lower mortality rate, though the difference did not reach a significant level. There was a significant negative correlation observed between plasma Zn level and 30-day mortality, along with another significant negative link between plasma CRP level before operation and Sepsis-related Organ Failure Assessment (SOFA) score. Other measured parameters were similar between the intervention and placebo groups.Conclusion: The patients undergoing CABG appeared to benefit from trace element supplementation. A brief period of Addamel administration following CABG could prevent a decrease in the serum concentration of trace elements and reduce the circulating plasma CRP.Clinical Trial Registration Number: IRCT2015110924975N1
Keywords: clinical outcome